Blended-Problem-Based Learning: How its impact on students' critical thinking skills? - Marheny Lukitasari; Indah Purnamasari; Sri Utami; Akhmad Sukri (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Critical thinking skills are one of the four main competencies that must be empowered in the 21st-century learning. This study aimed to describe students' critical thinking skills through the application of blended-problem-based learning (PBL) in the Cell Biology course. The data sources of this research were 28 students who were taking Cell Biology Course in Department of Biology Education, Universitas PGRI Madiun. The research instruments used were 1) observation sheet, 2) interview guidelines, and 3) critical thinking skills test. The study was designed by applying blended-PBL on 12 topics. The data analysis was performed in descriptive qualitative. The results showed that the application of blended-PBL was able to train students to improve their critical thinking skills in term of how to answer the test given. However, further studies need to be done with a wider number of samples and material scope to get more comprehensive information.